2020
DOI: 10.1109/access.2020.2994988
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight and Formally Secure Certificate Based Signcryption With Proxy Re-Encryption (CBSRE) for Internet of Things Enabled Smart Grid

Abstract: A smart grid is a new ecosystem, which is made by combining a number of smart Internet of Things (IoT) devices that manage wide energy sources by increasing the efficiency and reliability of the smart energy systems. As the IoT devices in the smart grid ecosystem generate a gigantic amount of data that needs to be stored and managed in the cloud server. On the other hand, the stored data in the cloud server can be accessible to a number of data users, therefore the data need authenticity and secrecy. Here, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
(79 reference statements)
0
30
0
Order By: Relevance
“…One part of the pair is called the secret value and the other part is called the partial private key. The secret value is randomly selected by the user, but the partial private key is calculated by KGC using its master secret key [18]. To authenticate the message, the signature generation algorithm requires both the keys of the user such as the secret value and the partial private key.…”
Section: Figure 2 Generic Illustration Of the Content Poisoning Attackmentioning
confidence: 99%
See 3 more Smart Citations
“…One part of the pair is called the secret value and the other part is called the partial private key. The secret value is randomly selected by the user, but the partial private key is calculated by KGC using its master secret key [18]. To authenticate the message, the signature generation algorithm requires both the keys of the user such as the secret value and the partial private key.…”
Section: Figure 2 Generic Illustration Of the Content Poisoning Attackmentioning
confidence: 99%
“…Note: the methods described above are mostly based on the concept of BPRG and ECC and therefore maintain high-cost complexities [18]. In addition, the schemes [26]- [36] do not have a concrete solution to their proposed applications.…”
Section: B Certificateless Signature Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ζ cannot replay the old messages because he/she needs fresh FNs for every new session. Furthermore, we compare our scheme with the existing CGS and ID-BGS schemes in milliseconds (ms) by using the above major operation, according to the experiments performed in [50] with the following hardware and software specifications: [50], an SPBPM will take 4.32 ms, a single SBP will take 14.90 ms, SEXP will take 1.25 ms, and SEPM will take 0.97 ms. Based on the experiments performed in [51,52], we consider that a SHEDM will take 0.48 ms. On the bases of the above expansive mathematical operations, we conduct the computation cost comparison of our proposed scheme with existing CGS schemes which are Zhang et al [28], Zhou et al [29], Zhang et al [30], Zhou [31], Waheed et al [32], and Karati et al [33] as shown in Tables 2 and 3. Further, the computation cost comparison of our proposed scheme with existing ID-BGS schemes which are Wei et al [21] and Shen et al [23] is shown in Tables 4 and 5.…”
Section: Forward Secrecymentioning
confidence: 99%